The impact of climate policy uncertainty on energy supply chain resilience - Nuoer, Suo; Long, Fei (Transformations In Business & Economics, 2026)
Amidst intensifying climate change concerns, frequent adjustments to climate policies present significant challenges to the stability and resilience of the energy supply chain. Uncertainty surrounding these policies exacerbates supply chain vulnerability, thereby threatening the sustainable development of the energy sector. This study employs econometric models analysing matched data from listed upstream and downstream firms to investigate the effects of climate policy uncertainty on supply-demand coordination, relationship stability, and the quality of supply-side innovation. The findings indicate that policy instability heightens uncertainty in production and procurement decisions, intensifying supply-demand fluctuations, reducing inter-firm cooperation, and weakening supply-demand relationships. Furthermore, it dampens demand for technological innovation, diminishing the supply quality and innovative capacity of upstream suppliers. The study concludes that enhancing supply chain resilience necessitates measures such as improving information sharing between upstream and downstream entities, optimising supply-demand coordination efficiency, and boosting collaborative innovation across the supply chain. Consequently, it is recommended to enhance policy stability and transparency and promote cross-sectoral cooperation and technological advancement to bolster the energy supply chain’s risk resilience and adaptability, ultimately aiding the energy sector in navigating the risks posed by climate policy uncertainty.